Strategi Produksi Film: Studi Kasus Nyanyian Pohon Lontar Program Layar Cerita Perempuan Indonesiana TV - Latif, Yusmita Akhirul; Anggra Agastyassa Owie (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the production strategy of the film Nyanyian Pohon Lontar, the winner of the “Layar Cerita Perempuan Indonesiana TV” competition, which was shot in Kupang, East Nusa Tenggara. The research setting focuses on the challenges of production outside the film industry center, including logistical limitations, equipment availability, and adaptation to local culture. The method used is a qualitative case study through in-depth interviews, participant observation, and analysis of production documents. The results of the study indicate three key strategies that support the success of the production: (1) collaboration between the central and local crew to integrate technical expertise with local cultural knowledge; (2) utilization of local resources in the provision of props, wardrobe, and sets; and (3) adaptation of the work process to the rhythm and customs of the community, including schedule adjustments and customary negotiations. These strategies proved effective in maintaining the smooth production while ensuring the authenticity of the representation of Kupang culture in the film.